The Effect of Geographical and Climatic Factors on the Distribution of Phlebotomus papatasi (Diptera: Psychodidae) in Golestan Province, an Endemic Focus of Zoonotic Cutaneous Leishmaniasis in Iran, 2014 - Ehsan Allah Kalteh; Aiuob Sofizadeh; Seyed Hamid Hosseini (Tehran University of Medical Sciences, 2022)
Background: Phlebotomus papatasi is known as the main vector of zoonotic cutaneous leishmaniasis. This study aimed to investigate the effect of geographical and bioclimatic factors on the Ph. papatasi distribution. Methods: A total of 34 villages were selected, and sampling was performed three times using 120 sticky traps in each selected village. All the collected species were mounted and identified. The densities of Ph. papatasi were measured in all the villages and entered ArcMap as a point layer. The required bioclimatic and environmental variables were extracted from the global climate database and The normalized difference vegetation index was obtained from the MODIS satellite imagery, also, all variables entered into ArcMap as raster layers, so The numerical value of each independent variable in the cell where the selected village is located in this, was extracted using spatial analyst tools and the value to point submenu. All the data were finally entered IBM SPSS, and the relationship was examined between the number of collected Ph. papatasi and the independent variables using Spearman's correlation test. Results: A total of 1773 specimens of Ph. papatasi were collected. The findings of this study showed that max temperature of the warmest month, temperature annual range, temperature seasonality, mean diurnal range, precipitation seasonality, mean temperature of the driest and warmest quarter were positively associated with the density of Ph. papatasi. Conclusion: Air temperature and precipitation were shown as the most significant factors in the distribution of Ph. papatasi.